2010
DOI: 10.2337/dc10-0368
|View full text |Cite|
|
Sign up to set email alerts
|

Increases in Waist Circumference and Weight As Predictors of Type 2 Diabetes in Individuals With Impaired Fasting Glucose: Influence of Baseline BMI

Abstract: OBJECTIVETo evaluate in impaired fasting glucose (IFG) the relative importance of increases in waist circumference and weight on progression to type 2 diabetes.RESEARCH DESIGN AND METHODSThe 9-year incidence of diabetes was studied in 979 men and women with baseline IFG, from the Data from an Epidemiological Study on the Insulin Resistance Syndrome (DESIR) cohort.RESULTSIncreases in both waist circumference and weight were significantly associated with diabetes incidence. Standardized odds ratios (95% CI) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
5
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 14 publications
(16 reference statements)
4
43
5
2
Order By: Relevance
“…Recently, WC has been recognized as a risk factor of diabetes incidence in IFG level. An interaction was observed between BMI category and the effect of WC increase on diabetes progression, with a larger impact in participants with BMIs b 25 kg/m 2 than in those with BMIs ≥25 kg/m 2 [17]. Our subjects had BMIs b25 kg/m 2 .…”
Section: Discussionmentioning
confidence: 85%
“…Recently, WC has been recognized as a risk factor of diabetes incidence in IFG level. An interaction was observed between BMI category and the effect of WC increase on diabetes progression, with a larger impact in participants with BMIs b 25 kg/m 2 than in those with BMIs ≥25 kg/m 2 [17]. Our subjects had BMIs b25 kg/m 2 .…”
Section: Discussionmentioning
confidence: 85%
“…Greater BMI and WC predispose to insulin resistance and diabetes and diabetes increases risk of cognitive impairment. 27,28 Another possible explanation is disruption of the blood-brain barrier by HIV since HIV proteins 29 alter the tight junctions of the blood-brain barrier, potentially increasing brain exposure to higher levels of glucose or other damaging molecules. While we found that CSF glucose levels were higher in diabetic than nondiabetic patients, the difference was not dramatic and seems unlikely to account for the dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, BMI < 23 is taken as nonobese and BMI ‡ 23-24.99 as overweight and > 25 as obese. Asian Indians also have higher tendency towards central obesity; therefore, WC and WHR are considered better indicators of progression to T2D in these ethnic groups, (Mohan et al, 2003;Gautier et al, 2010;Kamath et al, 2011;Liao et al, 2011). WC cut offs used in the present study are > 85 for males and > 80 for females; and for WHR the cut offs are > 0.89 for males and > 0.81 for females (Snehalatha et al, 2003).…”
Section: Resultsmentioning
confidence: 99%